Enhanced capacity of service providers in the deployment of RiceAdvice digital application - Ahouantona, Kokou; Guindo, Samuel; Dossou-Yovo, Elliott Ronald (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The RiceAdvice digital tool, which generates site-specific crop calendars, variety selection, and fertilizer recommendations, was taught to 99 service providers, including 12 women. Seventy-nine of the service providers were under the age of 40. The service providers' tasks include generating recommendations and supporting farmers in their application to 83,160 farmers from the Centers for Mechanized Agriculture using RiceAdvice tool during the rainy season of 2023. The use of RiceAdvice also facilitates farmers access to finances particularly loans from the banks as an insurance for good yields in the face of climate change. By enhancing the capacity of service providers in the use of RiceAdvice, AICCRA-Mali promotes the adoption of CSA and CIS, while creating jobs in Mali.